PENGEMBANGAN MULTIMEDIA POWER POINT BERBASIS ISPRING 8 PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Mutrikoh, Mutrikoh; Marzuki, Marzuki; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis thesis discusses the research finding result of developing multimedia of powerpoint based Ispring8 to mathematic learning in the elementary school. The presentresearch purposes to produce products in the form of valid, practical, and effectivecriteria and describe the ways of use and the obstacles encountered when usingmultimedia that was developed. The development research model used is a 4-D model(Define, Design, Develop, Disseminate) which has been adapted, namely thedevelopment research stages as follows (1) product discovery, (2) product manufacture,(3) product development and (4) product dissemination. Based on the explanation of theresults of research and discussion, conclusions can be obtained, namely (1) Theproducts compiled fulfill valid criteria with a value of 86.67; (2) Products arrangedpractically with a value of 79.375. (3) The products arranged can be used in learningand provide effective results in the assessment of knowledge and skills. The effectivenessin the results of the knowledge assessment is equal to 79.79 and the effectiveness in theresults of the skills assessment 83.67. (4) Constraints faced in the use of multimediadeveloped are the inadequate availability of computer equipment in primary schools sothat it affects the processing time by students.Keywords: Mathematic Learning, Multimedia Development